2018
DOI: 10.1108/ijdi-05-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and methods of financing for the development of local entrepreneurship in Iran

Abstract: Purpose The purpose of the current study is to investigate the public and private financing obstacles to medium- and small-scale entrepreneurs in rural areas in Iran. Design/methodology/approach Descriptive analytic research method is used for collecting field data among 5,770 owners of entrepreneurial businesses located in rural areas of Mashhad in 2015. Findings The results showed that there are numerous public and private obstacles in rural entrepreneurship financing in Iran, which are the main factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The literature has argued that social capital promotes rural entrepreneurship through financial availability and information accessibility. When private enterprises are in the earliest stages of existence, it is difficult for them to obtain support from formal institutions, while informal culture and tradition are particularly important (Xin and Pearce, 1994;Casson and Giusta, 2007) because rural households lack collateral, which reduces the possibility of rural household loans (Ahlstrom and Bruton, 2010;Schmalz et al, 2017;Sadeghloo et al, 2018). Rural households rely more on private financing (Jia et al, 2013;Hu and Zhang, 2014).…”
Section: Social Capital and Rural Entrepreneurshipmentioning
confidence: 99%
“…The literature has argued that social capital promotes rural entrepreneurship through financial availability and information accessibility. When private enterprises are in the earliest stages of existence, it is difficult for them to obtain support from formal institutions, while informal culture and tradition are particularly important (Xin and Pearce, 1994;Casson and Giusta, 2007) because rural households lack collateral, which reduces the possibility of rural household loans (Ahlstrom and Bruton, 2010;Schmalz et al, 2017;Sadeghloo et al, 2018). Rural households rely more on private financing (Jia et al, 2013;Hu and Zhang, 2014).…”
Section: Social Capital and Rural Entrepreneurshipmentioning
confidence: 99%
“…There are both theoretical and empirical grounds, for example, to suggest that important radical innovation is more likely to be affected by a large array of organizational capabilities (such as slack resources and network competence, e.g., Tang, Tang, Zhu, & Li, 2019;Yu, Hao, Ahlstrom, Si, & Liang, 2014) and environmental characteristics (such as dynamism and institutional uncertainty, e.g., Tomizawa, Zhao, Bassellier, & Ahlstrom, 2020). In addition, previous research indicated that innovation in Iran is more incremental due to many barriers to radical innovation such as limited or attenuated resourcesin terms of both technology and funding (Ahlstrom, Cumming, & Vismara, 2018;Sadeghloo, Sojasi Qeidari, Salehi, & Faal Jalali, 2018) and the perceived high social cost of radical innovation in the collective culture of Iran as well as other more formal institutional barriers (Kamalian, Rashki, & Arbabi, 2011;Peng, Ahlstrom, Carraher, & Shi, 2017).…”
Section: Entrepreneurial Alertness and Firm Innovationmentioning
confidence: 99%
“…This leads researchers to further interpret their limitations from various perspectives, some of which need an interaction of external factors such as losing entrepreneurial opportunities and local view toward entrepreneurship with individual factors such as social merits (Thompson et al, 2000), effectiveness and its impact on successful or unsuccessful entrepreneurial businesses (Hoyos-Ruperto et al, 2013). Although national governments invest in initiatives aimed at encouraging rural entrepreneurship on the assumption that it contributes to competitiveness and employment (Kasabov, 2016) but factors may sometimes be caused by inappropriate conditions and legal and financial problems (Sadeghloo et al, 2018). Unstable governmental policies and changes in these policies, lack of governmental support, complex regulations, inadequate regulations, unstable economy of the country and international sanctions on the one hand and lack of coordination between business partners and high tax rates could increase the IJLMA 62,1 fear of low profit and discourage entrepreneurs.…”
Section: Factors Affecting Failure Of Local Entrepreneursmentioning
confidence: 99%
“…Entrepreneurs mostly have to conduct financial analyses to get better efficiency despite the risk. However, in a conventional market in which market agents has access to information, high level of efficiency comes with a high level of risk and this necessitates the existence of a business plan (Sadeghloo et al, 2018). The proposed structure for business plan development, based on any approach or guideline, should be flexible, with slight variations in different conditions and updated to suit business requirements.…”
Section: Factors Affecting Failure Of Local Entrepreneursmentioning
confidence: 99%